2016
DOI: 10.1515/topling-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

On the production of metaphors and metonymies by Jordanian EFL learners: acquisition and implications

Abstract: This study explores the ability of Jordanian learners of English as a foreign language (EFL) to produce English metaphorical and metonymical expressions, using a completion task. It also examines whether the use of conceptual and linguistic knowledge of the participants’ first language, i.e. Jordanian Arabic (JA) would facilitate the production task. The study adopts a contrastive model to compare and contrast figurative devices in English and JA, consisting of six types that vary in relation to the conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
1
29
0
2
Order By: Relevance
“…Based on our understanding of the Jordanian teaching context and the level of our students taking into account their educational background and exposure to English, we selected students with a GPA of 3.00 or higher because we believed that this procedure might provide more reliable data (cf. Altakhaineh & Zibin, ; Zibin, , ; Zibin & Altakhaineh, ). We also intended to select a homogenous group in terms of academic level in an attempt to cancel any intervening factors in the results we obtain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our understanding of the Jordanian teaching context and the level of our students taking into account their educational background and exposure to English, we selected students with a GPA of 3.00 or higher because we believed that this procedure might provide more reliable data (cf. Altakhaineh & Zibin, ; Zibin, , ; Zibin & Altakhaineh, ). We also intended to select a homogenous group in terms of academic level in an attempt to cancel any intervening factors in the results we obtain.…”
Section: Methodsmentioning
confidence: 99%
“…The difficulty is not merely attributed to acquiring enough vocabulary that will enable students to convey their ideas effectively in writing; it also includes their knowledge of certain aspects of discourse, for example, clause combining (see Veronique, ). On the basis of our experience as teachers of English as a foreign language, some of the challenges facing teachers in Jordan are the English teaching methods followed at school and to a certain extent at university level (see Zibin, ). Traditional teaching methods have made students over dependant on teachers, lacking self‐independence.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the results, the two researchers reported that cultural awareness of the figurative expressions of the target language may contribute considerably to the development of communicative competence, in addition to other language skills. In her study, Zibin (2016) explores the ability of Jordanian learners of English as a foreign language learners to produce English metaphorical expressions, and whether participants" knowledge of conceptual and linguistic metaphors of their mother tongue Jordanian have an influence on the production of metaphorical expressions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In most cases, metaphors that express emotions are quite frequent because in almost cases they emotions are integrated within the in humans" lives. [However], the time it is not used frequently in everyday experiences, then its frequency will not be high (Zibin 2016).…”
Section: Angermentioning
confidence: 99%
“…The second section consists of two questions that test the participants' production of different loanwords (see Appendix A). The questions of the second section are written in Emirati Arabic and they aim to test the participants' productive skills (see also Zibin, 2016). These questions require one-word or two-word (e.g.…”
Section: The Testmentioning
confidence: 99%